CFD-based simulation of thermal distribution of indoor environment - Wang, Wei (2018)
It is important to analyse the thermal distribution of the indoor environment in Singapore, which has a tropical rain forest climate, as it affects our day-to-day lives. Nowadays, Heating, Ventilating and Air-Conditioning (HVAC) systems are increasingly used in office, school and industrial buildings. HVAC systems can maintain humans’ thermal comfort by lowering humidity, cooling or heating the air temperatures. With the application of Computational Fluid Dynamics (CFD), an ideal air flow can be simulated in the room. This report presents how the configuration of ventilation will affect the thermal distribution of the indoor environment by simulation using CFD. The study was conducted in a systematic way using steady-state transit simulation in a 3-Dimensional (3D) room. A manikin was added in the room to simulate the thermal comfort of humans. The result was obtained by comparing the velocity vector, velocity contour and temperature contour. The results show that different configurations of ventilation affect the thermal comfort of humans. Several analyses that stated that displacement ventilation is a trend in indoor environment were proved. By collecting and comprising the results are obtained, it shows that displacement ventilation is more suitable to maintain the thermal comfort of humans when compared to mixed ventilation in the indoor environment. The findings confirm the analyses made by other researchers as well.